Optimal load shedding in loss minimization by using multistage artificial intelligence / Nur Amalina Rahmad - Rahmad, Nur Amalina (2013)
Voltage collapse is one of the problems in power system. It can even cause blackout and bring serious negative feedback to consumers especially for industrial sector. Everything is counted when it comes or involves money. Therefore it is important to ensure the stability of the system. Optimization in load shedding is proposed to enhance voltage stability. Increases in load demand, disturbance or changes in power system operational will ascend the instability of the voltage [1].